Інтертекстуальність малої прози Х. Л. Борхеса - Дзись, Г. (Питання літературознавства, 2009)
Мала проза Х. Л. Борхеса аналізується в аспекті її інтертекстуальності. Особлива увага звертається на дослідження місця та ролі інтертексту, нелінійного письма як ключових засад творчості латиноамериканського письменника. Зазначається, що інтертекстуальність у прозі митця виражена найрізноманітнішими формами (цитати, алюзії, ремінісценції тощо). Водночас простежено, як у борхесівських оповіданнях та мініатюрах відбито міфосинкретичні структури мислення, що поєднують різні часи та простори. Розвинуто думку про те, що інтертекстуальність творів Борхеса співвідноситься з концепцією „лабіринту”. Суттєвим концептуальним підґрунтям статті слугують теоретичні праці Р. Барта, Ю. Крістєвої, М. Бахтіна, О. Астаф’єва, Л. Біловус та ін. The article deals with the investigation of the intertextual field of the small prose by Latin American writer J. L. Borges. On the basis of works of foreign and Ukrainian scholars (R. Barthes, J. Kristeva, M. Bakhtin, O.Astafiev, L. Bilovuss and others) the author considers theoretical and aesthetic aspects of the intertextuality. The main attention is paid to the determination of the role and place of the intertext as the fundamental feature of the creative process of writer. The basic forms of the intertextuality (citations, allusions, reminiscences) are analysed on different functional levels of the Borges’ text. The attention is paid to the analysis of the artistic features of the representation of the author’s world-view and the ways of the author’s selfexpression. The author concedes that intertext in the prosaic miniatures by J. L. Borges correlates with the concept of labyrinth.